Neutrophil phenotypes and functions in cancer: A consensus statement - Quail, Daniela F; Amulic, Borko; Aziz, Monowar; Barnes, Betsy J; Eruslanov, Evgeniy; Fridlender, Zvi G; Goodridge, Helen S; Granot, Zvi; Hidalgo, Andrés; Huttenlocher, Anna; Kaplan, Mariana J; Malanchi, Ilaria; et al. (The Journal of experimental medicine, 2022)
Neutrophils are the first responders to infection and inflammation and are thus a critical component of innate immune defense. Understanding the behavior of neutrophils as they act within various inflammatory contexts has provided insights into their role in sterile and infectious diseases; however, the field of neutrophils in cancer is comparatively young. Here, we summarize key concepts and current knowledge gaps related to the diverse roles of neutrophils throughout cancer progression. We discuss sources of neutrophil heterogeneity in cancer and provide recommendations on nomenclature for neutrophil states that are distinct in maturation and activation. We address discrepancies in the literature that highlight a need for technical standards that ought to be considered between laboratories. Finally, we review emerging questions in neutrophil biology and innate immunity in cancer. Overall, we emphasize that neutrophils are a more diverse population than previously appreciated and that their role in cancer may present novel unexplored opportunities to treat cancer.